A novel structural maintenance of chromosomes (SMC)-related protein family specific to Archaea - Yoshinaga, Mari; Nakayama, Takuro; Inagaki, Yuji (Frontiers in Microbiology, 2022)
The ATPases belonging to the SMC superfamily are involved in the maintenance of chromosome organization and dynamics, as well as DNA repair. The major proteins in this superfamily recognized to date are either conserved among the three domains of Life (i.e., SMC and Rad50) or specific to Bacteria (i.e., RecF, RecN, and MukB). In Archaea, no protein related to SMC (SMC-related protein) with a broad taxonomic distribution has been reported. Nevertheless, two SMC-related proteins, namely coalescin and Sph, have been identified in crenarchaea Sulfolobus spp. and the euryarchaeon Halobacterium salinarum, respectively, hinting that the diversity of SMC-related proteins has been overlooked in Archaea. In this study, we report a novel SMC-related protein that is distributed among broad archaeal lineages and termed “Archaea-specific SMC-related proteins” or “ASRPs.” We further demonstrate that the ASRP family encloses both coalescin and Sph but the two proteins represent only a tip of the diversity of this family.